A high-torque, lightweight, transparent EVA composite foam material for sports shoe soles and preparation method thereof
Through the EVA composite foaming material with high transparency modified copolymerization of PP and other components, the problem of degradation of comfort and rebound performance of sports sole materials after high-strength running is solved, and high torque resistance, fatigue resistance, transparent light quality is achieved Sole material improves wear comfort and sole stability.
Patent Information
- Application Number
- CN202310720594.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-16
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2043-06-16
AI Technical Summary
The existing sports sole materials have significantly reduced their comfort and rebound performance after high-strength running, resulting in poor sole stability, increasing the risk of knee wear, and insufficient transparency and specific gravity, affecting wear comfort.
EVA composite foaming material using components such as high transparency modified copolymer PP, ethylene-vinyl acetate copolymer, olefin block copolymer, wear-resistant agent and transparent foaming agent, and the thermoplastic elasticity of high transparency modified copolymer PP The body composite material formula and foaming process are used to prepare high torque-resistant, fatigue-resistant, transparent EVA composite foamed sole material with a specific gravity of less than 0.2g/cm3.
It achieves the stability and comfort of the sole after high-intensity exercise, extends the durability of the material's physical properties, reduces the risk of foot injury, and improves the lightweight, high rebound and anti-compression properties of the sole.
Smart Images

Figure CN116589784B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of foamed soles, and in particular to a high-torque, lightweight, transparent EVA composite foamed material for sports shoe soles and a preparation method thereof. Background Art
[0002] Various running shoes on the market have good comfort and rebound performance when they are first worn, but after 10KM of high-intensity running, their comfort and rebound performance usually drop significantly, the stability of the sole becomes worse, and it is easy to cause foot injuries. One of the reasons is that when the human body wears the shoes, the polymer materials are subjected to periodic dynamic loads and frequent repeated stress, which causes the physical properties of the materials to decline.
[0003] To this end, a Chinese patent document with publication number CN 110172202 A discloses a high torsion foam material, in which the EVA composite material includes: 30-60 parts of ethylene-vinyl acetate copolymer; 20-50 parts of special vinyl polyolefin elastomer; 8-12 parts of ethylene propylene rubber; 8-12 parts of ethylene octene block copolymer; 0.5-0.8 parts of peroxide crosslinking agent; 1-5 parts of foaming agent; 2-3 parts of active agent; the torsional stiffness of the special vinyl polyolefin elastomer is 9-25MPa. Although the high torque foam material has a certain improvement on the stability of the sole, it has poor transparency and the sole specific gravity is 0.23-0.28g / cm 3 , the sole is heavy. When a runner wears shoes with this sole material, he will feel that his feet are particularly heavy and he will lift his feet slowly. This is not only not conducive to running, but will also increase the burden on the knee joints, leading to increased wear and tear on the knee joints. Summary of the invention
[0004] In order to overcome the above technical problems, the present invention provides a high-torque, lightweight and transparent EVA composite foam material for sports shoe soles and a preparation method thereof. The EVA composite foam material provided in the present application is used as a midsole, and has high torque resistance, fatigue resistance, low specific gravity and good transparency. In meeting the reciprocating motion of the human body, because of the good torque resistance and fatigue resistance of the material, the wearing comfort of the shoe can be maintained and the stability of the sole can be maintained, which is conducive to meeting the comprehensive needs of consumers.
[0005] The present invention provides a high-torque, light-weight, transparent EVA composite foam material for sports shoe soles, which is prepared by foaming an EVA composite material. The EVA composite material comprises the following components in parts by mass:
[0006] 30-50 parts of highly transparent modified copolymer PP; 30-50 parts of ethylene-vinyl acetate copolymer; 15-25 parts of olefin block copolymer; 5-10 parts of anti-wear agent; 0.2-0.5 parts of stearic acid; 0.2-1 parts of stearate; 0.3-1.5 parts of bridging agent; 1.5-6.5 parts of transparent foaming agent;
[0007] The highly transparent modified copolymer PP is prepared by mixing and granulating highly transparent copolymer PP, isoprene rubber, EPDM rubber and stearic acid; the specific gravity of the high-torque, lightweight transparent EVA composite foam material for sports shoe soles is less than 0.2 g / cm 3 .
[0008] Preferably, the mass proportion of the high-transparency copolymer PP in the high-transparency modified copolymer PP is not less than 30%.
[0009] Preferably, the light transmittance of the high-transparency copolymer PP is not less than 90%, and the melting point is less than 135°C.
[0010] Preferably, the specific gravity of the ethylene-vinyl acetate copolymer is ≤0.95 g / cm 3 ; The specific gravity of the olefin block copolymer is ≤0.89g / cm 3 .
[0011] Preferably, the anti-wear agent is a pre-dispersed silicone masterbatch.
[0012] Preferably, the bridging agent is 1,4-di-tert-butyl peroxide isopropylbenzene.
[0013] Compared with the prior art, the present invention develops a torque-resistant, fatigue-resistant, lightweight, transparent EVA composite foam sole material with a specific gravity of less than 0.2g / cm 3 ; In parts by mass, the shoe material includes: 30-50 parts of highly transparent modified copolymer PP, 30-50 parts of ethylene-vinyl acetate copolymer, 15-25 parts of olefin block copolymer, 5-10 parts of wear-resistant agent, 0.2-0.5 parts of stearic acid, 0.2-1 parts of stearate, 0.3-1.5 parts of bridging agent and 1.5-6.5 parts of transparent foaming agent; wherein, the highly transparent modified copolymer PP is prepared by mixing and granulating highly transparent copolymer PP, isoprene rubber, EPDM rubber and stearic acid. The present invention adopts the above-mentioned formula of composite material containing highly transparent modified copolymer PP thermoplastic elastomer to obtain an ideal raw material function combination. After the formula is blended and foamed with highly transparent modified copolymer PP thermoplastic elastomer, a specific gravity of 0.13g / cm 3, rebound> 65%, no change in rebound after 150,000 bendings, average torsional force 0.9N / mm, rebound after fatigue, energy return after fatigue, high transmittance composite foam shoe material, forming excellent lightweight, high rebound, anti-torque, anti-fatigue, compression resistance and other properties, and achieved unexpected beneficial effects.
[0014] The embodiment of the present invention provides a method for preparing the high-torque, lightweight and transparent EVA composite foam material for sports shoe soles, comprising the following steps:
[0015] Weigh the material components by mass, including 30-50 parts of highly transparent modified copolymer PP, 30-50 parts of ethylene-vinyl acetate copolymer, 15-25 parts of olefin block copolymer, 5-10 parts of anti-wear agent, 0.2-0.5 parts of stearic acid, 0.2-1 parts of stearate, 0.3-1.5 parts of bridging agent and 1.5-6.5 parts of transparent foaming agent;
[0016] The weighed material components are mixed, granulated, and then foamed to obtain the high-torque, lightweight, transparent EVA composite foam material for the sports shoe sole.
[0017] Preferably, the highly transparent modified copolymer PP is prepared in the following manner:
[0018] Highly transparent copolymer PP, EPDM rubber and stearic acid are mixed at a temperature of 130-135°C, and mixed particles are obtained by granulation;
[0019] The mixed particles, isoprene rubber and stearic acid are kneaded and granulated again, and the re-granulation temperature is 110-115° C. to obtain highly transparent modified copolymer PP.
[0020] Preferably, the foaming is IP injection foaming, and the foaming temperature is 175-180°C.
[0021] Preferably, the foaming is MD molding foaming, wherein the small foaming temperature is 165-175°C and the MD molding temperature is 155-165°C.
[0022] Correspondingly, the embodiment of the present invention also provides a preparation method of the EVA composite foam material for the sports shoe sole. The production process of the high torque resistance, fatigue resistance, light weight, and transparent EVA composite foam sole material is simple. It only needs to load various material components into the ripper in order for mixing. The time is short and the operating conditions are suitable. The obtained composite foam sole material has excellent anti-bending, high fatigue resistance, high elasticity, light weight and other properties. Among them, the obtained mixed material is granulated and cooled, and then small foaming and directly formed in an oven for finalizing to obtain a finished sole; or the technical parameters are adjusted by an IP foaming molding machine, and a finished sole with the same effect can also be obtained. The sole of the sports shoe made by this technical solution has high anti-bending performance and anti-fatigue performance, and has high rebound, anti-compression and comfort, so that consumers will not reduce the physical properties of the shoes such as rebound and compression after repeated high-intensity exercise for 10 kilometers during wearing and exercising, so the comfort of the shoes of this application is guaranteed. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The finished IP sole product is made of the high-transparent copolymer PP of Example 4 of the present invention;
[0024] Figure 2 The finished IP sole is made from the modified homopolymer PP of Comparative Example 5 of the present invention. DETAILED DESCRIPTION
[0025] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
[0026] The present application provides a high-torque, lightweight, transparent EVA composite foam material for sports shoe soles, which is prepared by foaming an EVA composite material, wherein the EVA composite material comprises the following components in parts by weight:
[0027] 30-50 parts of highly transparent modified copolymer PP; 30-50 parts of ethylene-vinyl acetate copolymer; 15-25 parts of olefin block copolymer; 5-10 parts of anti-wear agent; 0.2-0.5 parts of stearic acid; 0.2-1 parts of stearate; 0.3-1.5 parts of bridging agent; 1.5-6.5 parts of transparent foaming agent;
[0028] The highly transparent modified copolymer PP is prepared by mixing and granulating highly transparent copolymer PP, isoprene rubber, EPDM rubber and stearic acid; the specific gravity of the high-torque, lightweight transparent EVA composite foam material for sports shoe soles is less than 0.2 g / cm 3 .
[0029] When a runner is running, the light shoes he wears will make him feel very comfortable; research has found that reducing the weight of a single shoe by 100 grams can help a runner increase his speed by 1% in five kilometers. Therefore, developing an anti-torque, anti-fatigue, lightweight, transparent EVA composite foam sole material can meet the needs of consumers in reciprocating motion, reduce the decline in the material's physical properties, allow the comfort performance to continue, stabilize the sole, reduce runners' foot injuries, and extend the decline of other physical properties. This is a trend with good market prospects.
[0030] The high torque, light and transparent EVA composite foam material for sports shoe soles provided by the embodiment of the present invention can be called anti-torque, anti-fatigue, light and transparent EVA composite foam sole material, etc., with a specific gravity of less than 0.2g / cm 3 The foaming material is mainly composed of EVA, and 30-50 parts by weight (preferably 35-40 parts) of highly transparent modified copolymer PP and other ingredients are added.
[0031] Preferably, the highly transparent modified copolymer PP is obtained according to the following steps:
[0032] 1) Weigh the following raw materials by mass: 60 PHR of high-transparent copolymer PP, 40 PHR of EPDM rubber, and 0.15 PHR of stearic acid;
[0033] 2) kneading all the ingredients weighed in step 1) for 15-20 minutes at a temperature of 130-135° C.;
[0034] 3) Granulating the mixture obtained in step 2) and storing it for 24 hours for use, the granulation time is 9-11 minutes, and the granulator temperature is 110° C.-115° C.;
[0035] 4) Weigh 70 PHR of the particles produced in step 3), 30 PHR of isoprene rubber, and 0.15 PHR of stearic acid according to mass fractions;
[0036] 5) kneading all the ingredients weighed in step 4) for 8-10 minutes at a temperature of 120-125° C.;
[0037] 6) Granulate the mixture obtained in step 5) and store it for 24 hours for standby use. The granulation time is 9-11 minutes and the granulator temperature is 110° C.-115° C. to obtain a highly transparent modified copolymer PP material.
[0038] In the process of preparing the highly transparent modified copolymer PP material, the highly transparent copolymer PP described in step 1) can be one or more of Formosa Plastics 3204, 3504, 3015, 1102, and INEOS KS351. The English abbreviation of polypropylene is PP, which is the thermoplastic resin with the lowest density. It can be divided into homopolymer polypropylene and copolymer polypropylene according to the ethylene content. Its homopolymer can be abbreviated as PPH, which is a polymer of a single propylene monomer; the copolymer of PP is abbreviated as PPC, which is a copolymer of propylene monomer and ethylene monomer. According to the distribution of ethylene monomers on the molecular chain, it can be divided into random copolymers (PPR) and block copolymers (PPB). PPH (homopolymer PP) has good rigidity, but poor impact resistance (brittle), poor toughness, especially poor low-temperature impact resistance, poor creep resistance, poor dimensional stability, easy aging, and poor long-term heat stability; PPB has good impact resistance, but poor creep resistance, and PPR has good impact resistance and creep resistance. Generally, no solvent is added to the preparation system, and the propylene monomer is subjected to liquid phase bulk polymerization in a tank reactor in a liquid state, while ethylene and propylene are subjected to gas phase copolymerization in a fluidized bed reactor.
[0039] Specifically, high-transparency copolymer PP is a copolymer of propylene monomer and a small amount of ethylene (1-4%) monomer under heating, pressure and catalyst; compared with homopolymer PP, it has good comprehensive performance, high fatigue resistance, high rigidity, good heat resistance, good dimensional stability, excellent low-temperature toughness and good transparency. Some embodiments of the present invention require a specific gravity of less than or equal to 0.9g / cm 3 , transmittance ≥ 90%, Vicat softening temperature ≤ 110℃, melting point ≤ 131℃, and high-transparency copolymer PP with heat deformation temperature of 55℃, is used in high-torque, fatigue-resistant, lightweight, transparent EVA composite foaming sole materials. It can make up for the physical properties of polymer materials that decrease under cyclic dynamic loads and frequent repeated stresses during human wearing of shoes, affecting wearing comfort, shoe resilience and compressibility and other comprehensive physical properties, and maintaining the durability of the physical properties of the sole materials.
[0040] In the embodiment of the present invention, the highly transparent copolymerized PP is mixed with isoprene rubber, EPDM rubber and stearic acid to form a highly transparent modified copolymerized PP thermoplastic elastomer composite material. The EPDM rubber in step 1) can be one or more commercially available products of Dow's 3745, 3760, and 3762. In step 4), the isoprene rubber can be one or more of Japan's IR2200, IR2200L, and IR2205.
[0041] Specifically, the EPDM rubber used for the above-mentioned copolymer PP modification is a copolymer of ethylene, propylene and a small amount of non-conjugated diene, which is a type of EPDM rubber, represented by EPDM (Ethylene Propylene Diene Monomer); because its main chain is composed of chemically stable saturated hydrocarbons, and only contains unsaturated double bonds in the side chain, it has excellent aging resistance such as ozone resistance, heat resistance, and weather resistance. It is used in high-flex, fatigue-resistant, lightweight, transparent EVA composite foam sole materials, which can improve the shortcomings of copolymer PP's poor aging, increase the material's rebound performance, and can be used as a solubilizer for copolymer PP and isoprene rubber. Further requirements: specific gravity ≤ 0.86g / cm 3 , the third monomer is ethylidene norbornene (ENB) 4-6.
[0042] In addition, the isoprene rubber is a high-performance rubber, which can be called isoprene rubber, polyisoprene rubber, synthetic natural rubber, etc. It has good elasticity, cold resistance (glass transition temperature -68°C) and high tensile strength, high transparency and uniform color. The preferred embodiment of the present invention requires that the specific gravity of isoprene rubber is 0.91g / cm 3 , Mooney viscosity 75-85ML1+4 (100℃)MU, cis-1,4 structure content 98%, non-polluting; used in high-bending, anti-fatigue, lightweight, transparent EVA composite foaming sole materials, can provide good rebound performance and anti-bending performance, etc.
[0043] Preferably, in the highly transparent modified copolymer PP material, the mass proportion of the highly transparent copolymer PP is at least 30%, which can ensure the high fatigue resistance, torque resistance and transparency of the composite material. In some embodiments, the physical properties of the highly transparent copolymer PP after modification include: density of 0.89 g / cm 3 , melting point 125℃, rebound 55%.
[0044] The formula of the highly transparent modified copolymer PP thermoplastic elastomer composite material described in the embodiment of the present invention is an EVA composite material, wherein ethylene-vinyl acetate copolymer (EVA) is 30 to 50 parts, preferably 35 to 45 parts; olefin block copolymer (OBC) is 15 to 25 parts, for example, 15 parts, 20 parts, 25 parts, etc.
[0045] Preferably, the ethylene vinyl acetate copolymer model is one or more of EVA7470M, EVA460, EVA40L-03, and EVA40W.
[0046] Specifically, the ethylene-vinyl acetate copolymer (also known as ethylene-vinyl acetate copolymer) introduces a vinyl acetate (VA) structure into the molecular chain, and the mass content can be 20-30%; more preferably, the VA content is 26%, and the specific gravity is required to be ≤0.948g / cm 3 , hardness 80°A, this material has excellent flexibility, high resilience, good ductility and processability.
[0047] Preferably, the olefin block copolymer is one or more of OBC9107, OBC9007, OBC9500 and OBC9077 produced by Dow Chemical of the United States.
[0048] Specifically, the olefin block copolymer is an elastomer, the main raw materials of which are octene and ethylene; the specific gravity may be required to be ≤0.877g / cm 3 , hardness 60-63°A, compression permanent deformation 49%. This material has excellent high and low temperature stability, resilience, compression deformation and fatigue resistance, especially good resilience and compressibility at high temperature. It is used in high-flexibility, fatigue-resistant, lightweight, transparent EVA composite foam sole materials. It can make up for the shortcomings of high-transparent PP in shrinkage, and reduce the heat generated by the sole due to twists and turns during exercise, which affects the resilience and compressibility and the durability of the comprehensive physical properties.
[0049] In parts by mass, the EVA composite material described in the embodiment of the present invention includes: 5 to 10 parts of an anti-wear agent; 0.2 to 0.5 parts of stearic acid; 0.2 to 1 parts of zinc stearate; 0.3 to 1.5 parts of a bridging agent; and 1.5 to 6.5 parts of a transparent foaming agent.
[0050] Preferably, the wear-resistant agent is a pre-dispersed silicone masterbatch wear-resistant agent, which can be 5.5 to 8 parts by weight. The key parameters of the pre-dispersed silicone masterbatch wear-resistant agent used in the embodiment of the present invention include: 60% silicone content, high content, the carrier is EVA with 18% VA content, easy to disperse, and moisture ≤ 0.05%. In the material formula, stearic acid and zinc stearate can play the role of lubrication and promoting cross-linking; the mass part of stearic acid is preferably 0.5PHR, and the mass part of zinc stearate is preferably 0.8PHR.
[0051] Preferably, the bridging agent is an odorless bridging agent, specifically BIPB (1,4-di-tert-butyl peroxide isopropylbenzene) from Aksu, and 0.7-0.9 PHR of the odorless bridging agent is used. The foaming agent used in the embodiment of the present invention is a transparent foaming agent, preferably 3 to 6 parts by mass; specifically, the transparent foaming agent is an odorless white powder, the component is dinitrosopentamethylenetetramine, the melting point is 130°C, and the relative density is 1.61 g / cm 3 During the molding process, a large amount of gas is decomposed by heat and evenly dispersed in the material, forming a light-transmitting effect on the appearance of the material after cooling.
[0052] In a preferred embodiment of the present invention, the above formula is blended with a highly transparent modified copolymer PP thermoplastic elastomer and foamed to obtain a specific gravity of 0.13 g / cm 3 , rebound> 65%, the rebound does not change after 150,000 bending times, the average torsional force is 0.9N / mm, it rebounds after fatigue, the energy returns after fatigue, and the high transmittance composite foam shoe material is easy to use.
[0053] In addition, an embodiment of the present invention provides a method for preparing a high-torque, fatigue-resistant, lightweight, transparent EVA composite foamed sole material, comprising the following steps:
[0054] 1) Weigh the following ingredients by mass, including 30-50 PHR of high-transparency modified PP material, 30-50 PHR of ethylene-vinyl acetate copolymer, 15-25 PHR of olefin block copolymer, 0.2-1 PHR of zinc stearate, 0.2-0.5 PHR of stearic acid, and 5-10 PHR of anti-wear agent;
[0055] 2) kneading all the ingredients weighed in step 1) for 8-10 minutes at a temperature of 115-120° C.;
[0056] 3) Weigh the following ingredients by mass: 0.75 PHR of odorless bridging agent and 4.8 PHR of transparent foaming agent;
[0057] 4) adding all the ingredients weighed in step 3) to the mixed material in step 2) and mixing them for 5-7 minutes at a temperature of 120-125° C.;
[0058] 5) granulating the mixture obtained in step 4) for 9-11 minutes at a temperature of 100° C.-105° C.;
[0059] 6) Foaming the mixed particles obtained in step 5), with IP injection foaming time of 400-450 seconds and foaming temperature of 175° C.-180° C.; or, secondary small foaming time of 600-650 seconds and foaming temperature of 170° C.-175° C., and then MD molding to obtain.
[0060] Preferably, the equipment for mixing in step 2) is a linoleum mill; preferably, the equipment for granulation in step 5) is a twin-screw extruder granulator. In addition, PHR represents the number of parts added per 100 parts (by mass) of resin or rubber. In addition, the present invention has no special restrictions on the mold structure, thickness, size, texture and other parameters of the sole material, and conventional ones can be used.
[0061] In some embodiments, the foaming adopts the IP process; specifically, the obtained mixed particles are poured into the hopper of the IP injection machine (the injection machine temperature is 175-180°C, the machine clamping force is 120bar, the injection pressure is 90bar, the mold opening speed is 60%, and the four-stage temperature of the injection gun is 84°C, 86°C, 88°C, and 90°C) for injection foaming. The IP injection foaming time is 400-450 seconds, and the foaming temperature is 175°C-180°C, so that a high-torque, anti-fatigue, lightweight, transparent EVA composite foaming material IP sole can be obtained.
[0062] In some other embodiments, the foaming is performed by MD process; specifically, the obtained particles are poured into the required small foaming mold for foaming (the temperature of the small foaming machine is 165-175°C and the pressure is 150-170 kg / cm 2 , MD small foaming time is 600-650 seconds); the foamed small foam is cleaned and stored for 12 hours, then put into the MD molding machine for heating for 420 seconds, and then cooled for 420 seconds (MD molding machine temperature is 155-165°C, cooling temperature is 11-17°C), and a high-torque, anti-fatigue, lightweight, transparent EVA composite foam material MD sole is obtained.
[0063] The production process of the high torque resistance, fatigue resistance, lightweight, transparent EVA composite foam sole material of the embodiment of the present invention is simple; the obtained foam sole composite material has excellent anti-bending property, high fatigue resistance, high elasticity, low specific gravity, high transmittance and other properties, such as specific gravity of 0.13-0.17g / cm 3 , hardness 45-50C, rebound greater than 50%. The soles of sports shoes made with this technical solution not only have high anti-bending and anti-fatigue properties, but also have high rebound, anti-compression and comfort, so that consumers can reduce the degree of reduction in physical properties such as rebound and compression after repeated high-intensity exercise for 10 kilometers while wearing the shoes, thereby improving the wearing comfort.
[0064] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention. In the present invention, unless otherwise specified, the amounts involved in the present invention are all mass percentages. According to the composite foam material and preparation method thereof described above, different formulation examples can be selected in the embodiments of the present invention to meet the requirements of different products. In the following embodiments, a variety of different formulation examples of high torque resistance, fatigue resistance, lightweight, transparent EVA composite foam sole materials and their preparation processes are shown.
[0065] Among them, the specific gravity of high transparent copolymer PP is less than or equal to 0.9g / cm 3 , light transmittance ≥ 90%, Vicat softening temperature ≤ 110℃, melting point ≤ 131℃, thermal deformation temperature 55℃. EPDM rubber specific gravity ≤ 0.86g / cm 3, the third monomer is ethylidene norbornene (ENB) 4-6. Isoprene rubber specific gravity 0.91g / cm 3 , Mooney viscosity 75-85ML1+4 (100℃)MU, cis 1,4 structure content 98%.
[0066] Ethylene vinyl acetate copolymer (EVA) VA content is 26%, specific gravity is 0.948g / cm 3 , hardness 80°A, melt index 6.9g / 10min. Olefin block copolymer OBC specific gravity 0.877g / cm 3 , hardness 63°A, melt index 5g / 10min. Transparent foaming agent is odorless white powder, melting point 130℃, relative density 1.61g / cm 3 Wear-resistant pre-dispersed silicone masterbatch, silicone content 60%, high content, carrier is EVA with VA content 18%, easy to disperse, moisture ≤ 0.05%; odorless bridging agent is BIPB from Aksu. The above raw materials are all commercially available.
[0067] Example 1 (MD)
[0068] A highly torque-resistant, fatigue-resistant, lightweight, transparent EVA composite foamed sole material is prepared by foaming a highly transparent modified PP thermoplastic elastomer composite material, wherein the highly transparent modified PP thermoplastic elastomer composite material comprises the following components in parts by weight:
[0069] Highly transparent modified copolymer PP: 35PHR, ethylene-vinyl acetate copolymer: 40PHR, olefin block copolymer: 25PHR, wear-resistant agent: 6PHR, stearic acid: 0.2PHR, zinc stearate: 0.8PHR, odorless bridging agent: 0.7PHR, transparent foaming agent: 5.8PHR.
[0070] The process of preparing highly transparent modified copolymer PP includes the following steps:
[0071] 1) Weigh the following ingredients by mass: high transparent copolymer PP KS351 60PHR, EPDM rubber 374540PHR, stearic acid 0.15PHR;
[0072] 2) kneading all the ingredients weighed in step 1) for 15-20 minutes at a temperature of 130-135° C.;
[0073] 3) Granulating the mixture obtained in step 2) and storing it for 24 hours for use, the granulation time is 9-11 minutes, and the granulator temperature is 110° C.-115° C.;
[0074] 4) Weigh 70 PHR of the particles produced in step 3), 30 PHR of isoprene rubber, and 0.15 PHR of stearic acid according to mass fractions;
[0075] 5) kneading all the ingredients weighed in step 4) for 8-10 minutes at a temperature of 120-125° C.;
[0076] 6) Granulate the mixture obtained in step 5) and store it for 24 hours for use. The granulation time is 9-11 minutes and the temperature of the granulator is 110°C-115°C to obtain a highly transparent modified copolymer PP material (after modification: density 0.89g / cm 3 , melting point 125°C, rebound 55%).
[0077] The preparation steps of the foamed sole material are as follows:
[0078] 1) Weigh the following ingredients by mass, including 35 PHR of high-transparent modified copolymer PP material, 40 PHR of ethylene vinyl acetate copolymer, 25 PHR of olefin block copolymer, 0.8 PHR of zinc stearate, 0.2 PHR of stearic acid, and 6 PHR of wear-resistant agent;
[0079] 2) kneading all the ingredients weighed in step 1) for 8-10 minutes at a temperature of 115-120° C.;
[0080] 3) Weigh the following ingredients by mass: 0.7 PHR of odorless bridging agent and 5.8 PHR of transparent foaming agent;
[0081] 4) adding all the ingredients weighed in step 3) to the mixed material in step 2) and mixing them for 5-7 minutes at a temperature of 120-125° C.;
[0082] 5) granulating the mixture obtained in step 4) for 9-11 minutes at a temperature of 100° C.-105° C.;
[0083] 6) Pour the particles obtained in step 5) into the required small foaming mold for foaming. The temperature of the small foaming machine is 165-175°C and the pressure is 170±5kg / cm 2 , MD small foaming time is 600-650 seconds;
[0084] The expanded small foams were cleaned and stored for 12 hours, placed in an MD molding machine for heating for 420 seconds, and cooled for 420 seconds. The temperature of the MD molding machine was 155-165° C., and the cooling temperature was 11-17° C., to obtain a high-torque, fatigue-resistant, lightweight, transparent EVA composite foam material MD sole.
[0085] Example 2 (MD)
[0086] A highly torque-resistant, fatigue-resistant, lightweight, transparent EVA composite foamed sole material is prepared by foaming a highly transparent modified PP thermoplastic elastomer composite material, wherein the highly transparent modified PP thermoplastic elastomer composite material comprises the following components in parts by weight:
[0087] Highly transparent modified copolymer PP: 40PHR, ethylene-vinyl acetate copolymer: 45PHR, olefin block copolymer: 15PHR, wear-resistant agent: 5.5PHR, stearic acid: 0.2PHR, zinc stearate: 0.8PHR, odorless bridging agent: 0.8PHR, transparent foaming agent: 6.2PHR.
[0088] The process of preparing highly transparent modified copolymer PP includes the following steps:
[0089] 1) Weigh the following ingredients by mass: high transparent copolymer PP KS351 60PHR, EPDM rubber 374540PHR, stearic acid 0.15PHR;
[0090] 2) kneading all the ingredients weighed in step 1) for 15-20 minutes at a temperature of 130-135° C.;
[0091] 3) Granulating the mixture obtained in step 2) and storing it for 24 hours for use, the granulation time is 9-11 minutes, and the granulator temperature is 110° C.-115° C.;
[0092] 4) Weigh 70 PHR of the particles produced in step 3), 30 PHR of isoprene rubber, and 0.15 PHR of stearic acid according to mass fractions;
[0093] 5) kneading all the ingredients weighed in step 4) for 8-10 minutes at a temperature of 120-125° C.;
[0094] 6) Granulate the mixture obtained in step 5) and store it for 24 hours for standby use. The granulation time is 9-11 minutes and the granulator temperature is 110° C.-115° C. to obtain a highly transparent modified copolymer PP material.
[0095] The preparation steps of the foamed sole material are as follows:
[0096] 1) Weigh the following ingredients by mass, including 40 PHR of high-transparent modified copolymer PP material, 45 PHR of ethylene vinyl acetate copolymer, 15 PHR of olefin block copolymer, 0.8 PHR of zinc stearate, 0.2 PHR of stearic acid, and 5.5 PHR of wear-resistant agent;
[0097] 2) kneading all the ingredients weighed in step 1) for 8-10 minutes at a temperature of 115-120° C.;
[0098] 3) Weigh the following ingredients by mass: 0.8 PHR of odorless bridging agent and 6.2 PHR of transparent foaming agent;
[0099] 4) adding all the ingredients weighed in step 3) to the mixed material in step 2) and mixing them for 5-7 minutes at a temperature of 120-125° C.;
[0100] 5) granulating the mixture obtained in step 4) for 9-11 minutes at a temperature of 100° C.-105° C.;
[0101] 6) Pour the particles obtained in step 5) into the required small foaming mold for foaming. The temperature of the small foaming machine is 165-175°C and the pressure is 170±5kg / cm 2 , MD small foaming time is 600-650 seconds;
[0102] The expanded small foams were cleaned and stored for 12 hours, placed in an MD molding machine for heating for 420 seconds, and cooled for 420 seconds. The temperature of the MD molding machine was 155-165° C., and the cooling temperature was 11-17° C., to obtain a high-torque, fatigue-resistant, lightweight, transparent EVA composite foam material MD sole.
[0103] Comparative Example 1 (MD)
[0104] The traditional MD lightweight transparent composite material on the market includes the following components by weight:
[0105] Polyolefin elastomer: 17PHR, ethylene-vinyl acetate copolymer: 50PHR, olefin block copolymer: 25PHR, EPDM rubber: 8PHR, wear-resistant agent: 6PHR, stearic acid: 0.2PHR, zinc stearate: 0.8PHR, odorless bridging agent: 0.7PHR, transparent foaming agent: 4.8PHR.
[0106] Polyolefin elastomer POE: specific gravity 0.889g / cm 3 , melt index 3g / 10min, hardness 95°A; EVA, OBC, EPDM, wear resistance agent and other component parameters are the same as those in Example 1 (the following comparative examples remain consistent).
[0107] The preparation steps are as follows:
[0108] 1) Weigh the following ingredients by mass: 17 PHR of polyolefin elastomer; 50 PHR of ethylene-vinyl acetate copolymer; 25 PHR of olefin block copolymer; 8 PHR of EPDM rubber; 6 PHR of anti-wear agent; 0.2 PHR of stearic acid; and 0.8 PHR of zinc stearate;
[0109] 2) kneading all the ingredients weighed in step 1) for 8-10 minutes at a temperature of 95-105° C.;
[0110] 3) Weigh the following ingredients by mass: 0.7 PHR of odorless bridging agent and 4.8 PHR of transparent foaming agent;
[0111] 4) adding all the ingredients weighed in step 3) to the mixed material in step 2) and mixing them for 5-7 minutes at a temperature of 115-118° C.;
[0112] 5) granulating the mixture obtained in step 4) for 9-11 minutes at a temperature of 100° C.-105° C.;
[0113] 6) Pour the particles obtained in step 5) into the required small foaming mold for foaming. The temperature of the small foaming machine is 165-175°C and the pressure is 150-170kg / cm 2 , MD small foaming time is 600-650 seconds;
[0114] The foamed small foam is cleaned and stored for 12 hours, put into the MD molding machine for heating for 420 seconds, and cooled for 420 seconds. The temperature of the MD molding machine is 155-165° C., and the cooling temperature is 11-17° C. to obtain a transparent foamed MD sole.
[0115] The following table lists the formula of high torque anti-fatigue lightweight transparent EVA composite foam material MD sole (Example 1-Example 1, Example 2-Example 2), and the formula of traditional transparent foam MD sole (Comparative Example 1):
[0116] Table 1 Formulas of Examples 1-2 of the present invention and Comparative Example 1
[0117]
[0118] Example 3 (IP injection)
[0119] A highly torque-resistant, fatigue-resistant, lightweight, transparent EVA composite foamed sole material is prepared by foaming a highly transparent modified PP thermoplastic elastomer composite material, wherein the highly transparent modified PP thermoplastic elastomer composite material comprises the following components in parts by weight:
[0120] Highly transparent modified copolymer PP: 48PHR, ethylene-vinyl acetate copolymer: 30PHR, olefin block copolymer: 22PHR, wear-resistant agent: 5.2PHR, stearic acid: 0.2PHR, zinc stearate: 0.8PHR, odorless bridging agent: 0.85PHR, transparent foaming agent: 4.2PHR.
[0121] The process of preparing highly transparent modified copolymer PP includes the following steps:
[0122] 1) Weigh the following ingredients by mass: high transparent copolymer PP KS351 60PHR, EPDM rubber 374540PHR, stearic acid 0.15PHR;
[0123] 2) kneading all the ingredients weighed in step 1) for 15-20 minutes at a temperature of 130-135° C.;
[0124] 3) Granulating the mixture obtained in step 2) and storing it for 24 hours for use, the granulation time is 9-11 minutes, and the granulator temperature is 110° C.-115° C.;
[0125] 4) Weigh 70 PHR of the particles produced in step 3), 30 PHR of isoprene rubber, and 0.15 PHR of stearic acid according to mass fractions;
[0126] 5) kneading all the ingredients weighed in step 4) for 8-10 minutes at a temperature of 120-125° C.;
[0127] 6) Granulate the mixture obtained in step 5) and store it for 24 hours for standby use. The granulation time is 9-11 minutes and the granulator temperature is 110° C.-115° C. to obtain a highly transparent modified copolymer PP material.
[0128] The steps for preparing the foaming sole material are as follows:
[0129] 1) Weigh the following ingredients by mass, including high transparent modified copolymer PP: 48PHR, ethylene-vinyl acetate copolymer: 27PHR, olefin block copolymer: 25PHR, wear-resistant agent: 5.2PHR, stearic acid: 0.2PHR, zinc stearate: 0.8PHR;
[0130] 2) kneading all the ingredients weighed in step 1) for 8-10 minutes at a temperature of 115-120° C.;
[0131] 3) Weigh the following ingredients by mass: 0.85 PHR of odorless bridging agent and 4.2 PHR of transparent foaming agent;
[0132] 4) adding all the ingredients weighed in step 3) to the mixed material in step 2) and mixing them for 5-7 minutes at a temperature of 120-125° C.;
[0133] 5) granulating the mixture obtained in step 4) for 9-11 minutes at a temperature of 100° C.-105° C.;
[0134] 6) Pour the mixed particles obtained in step 5) into the hopper of the IP injection machine, the injection machine temperature is 175-180° C., the machine clamping force is 120 bar, the injection pressure is 90 bar, the mold opening speed is 60%, the four-stage temperature of the injection gun is 84° C., 86° C., 88° C., and 90° C., and the IP injection foaming time is 400-450 seconds, and the foaming temperature is 175° C.-180° C. to obtain a high-torque, anti-fatigue, lightweight, transparent EVA composite foam material IP sole.
[0135] Example 4 (IP injection)
[0136] A highly torque-resistant, fatigue-resistant, lightweight, transparent EVA composite foamed sole material is prepared by foaming a highly transparent modified PP thermoplastic elastomer composite material, wherein the highly transparent modified PP thermoplastic elastomer composite material comprises the following components in parts by weight:
[0137] Highly transparent modified copolymer PP: 52PHR, ethylene-vinyl acetate copolymer: 23PHR, olefin block copolymer: 25PHR, wear-resistant agent: 6PHR, stearic acid: 0.2PHR, zinc stearate: 0.8PHR, odorless bridging agent: 0.92PHR, transparent foaming agent: 4.5PHR.
[0138] The process of preparing highly transparent modified copolymer PP includes the following steps:
[0139] 1) Weigh the following ingredients by mass: high transparent copolymer PP KS351 60PHR, EPDM rubber 374540PHR, stearic acid 0.15PHR;
[0140] 2) kneading all the ingredients weighed in step 1) for 15-20 minutes at a temperature of 130-135° C.;
[0141] 3) Granulating the mixture obtained in step 2) and storing it for 24 hours for use, the granulation time is 9-11 minutes, and the granulator temperature is 110° C.-115° C.;
[0142] 4) Weigh 70 PHR of the particles produced in step 3), 30 PHR of isoprene rubber, and 0.15 PHR of stearic acid according to mass fractions;
[0143] 5) kneading all the ingredients weighed in step 4) for 8-10 minutes at a temperature of 120-125° C.;
[0144] 6) Granulate the mixture obtained in step 5) and store it for 24 hours for standby use. The granulation time is 9-11 minutes and the granulator temperature is 110° C.-115° C. to obtain a highly transparent modified copolymer PP material.
[0145] The steps for preparing the foaming sole material are as follows:
[0146] 1) Weigh the following ingredients by mass, including high transparent modified copolymer PP: 52PHR, ethylene-vinyl acetate copolymer: 23PHR, olefin block copolymer: 25PHR, wear-resistant agent: 6PHR, stearic acid: 0.2PHR, zinc stearate: 0.8PHR;
[0147] 2) kneading all the ingredients weighed in step 1) for 8-10 minutes at a temperature of 115-120° C.;
[0148] 3) Weigh the following ingredients by mass: 0.92 PHR of odorless bridging agent and 4.5 PHR of transparent foaming agent;
[0149] 4) adding all the ingredients weighed in step 3) to the mixed material in step 2) and mixing them for 5-7 minutes at a temperature of 120-125° C.;
[0150] 5) granulating the mixture obtained in step 4) for 9-11 minutes at a temperature of 100° C.-105° C.;
[0151] 6) Pour the mixed particles obtained in step 5) into the hopper of the IP injection machine, the injection machine temperature is 175-180° C., the machine clamping force is 120 bar, the injection pressure is 90 bar, the mold opening speed is 60%, the four-stage temperature of the injection gun is 84° C., 86° C., 88° C., and 90° C., and the IP injection foaming time is 400-450 seconds, and the foaming temperature is 175° C.-180° C. to obtain a high-torque, anti-fatigue, lightweight, transparent EVA composite foam material IP sole.
[0152] Comparative Example 2 (IP Injection)
[0153] The lightweight transparent composite material on the market includes the following components by weight:
[0154] Polyolefin elastomer: 20PHR, ethylene-vinyl acetate copolymer: 58PHR, olefin block copolymer: 22PHR, EPDM rubber: 8PHR, wear-resistant agent: 6PHR, stearic acid: 0.5PHR, zinc stearate: 0.8PHR, odorless bridging agent: 0.65PHR, transparent foaming agent: 4.5PHR.
[0155] The preparation steps are as follows:
[0156] 1) Weigh the following ingredients by mass, including polyolefin elastomer: 20 PHR; ethylene-vinyl acetate copolymer: 58 PHR; olefin block copolymer: 22 PHR; EPDM rubber: 8 PHR; anti-wear agent: 6 PHR, stearic acid: 0.5 PHR, zinc stearate: 0.8 PHR;
[0157] 2) kneading all the ingredients weighed in step 1) for 8-10 minutes at a temperature of 95-105° C.;
[0158] 3) Weigh the following ingredients by mass: 0.65 PHR of odorless bridging agent and 4.5 PHR of transparent foaming agent.
[0159] 4) adding all the ingredients weighed in step 3) to the mixed material in step 2) and mixing them for 5-7 minutes at a temperature of 115-118° C.;
[0160] 5) granulating the mixture obtained in step 4) for 9-11 minutes at a temperature of 100° C.-105° C.;
[0161] 6) Pour the mixed particles obtained in step 5) into the hopper of the IP injection machine, the injection machine temperature is 175-180°C, the machine clamping force is 120 bar, the injection pressure is 90 bar, the mold opening speed is 60%, the four-stage temperature of the injection gun is 84°C, 86°C, 88°C, and 90°C, and the IP injection foaming time is 400-450 seconds, and the foaming temperature is 175°C-180°C to obtain a transparent foamed IP sole.
[0162] The following table lists the formulas of high torque, anti-fatigue, lightweight, transparent EVA composite foam IP soles (Example 1-Example 3, Example 2-Example 4), and the formula of traditional transparent foam IP soles (Comparative Example 2):
[0163] Table 2 Formulas of Examples 3-4 of the present invention and Comparative Example 2
[0164]
[0165] The physical properties of the EVA foam materials obtained in Examples 1-4 and Comparative Examples 1-2 were tested. The results are shown in Table 3. The test conditions were a temperature of 23±3° C. and a humidity of 65±5%.
[0166] Table 3 Physical properties of EVA foam materials of various embodiments and comparative examples
[0167]
[0168]
[0169] In the present invention, each embodiment adds a highly transparent modified copolymer PP composite material, and the comparative example adds a conventional polyolefin elastomer, wherein, Embodiments 1, 2 and Comparative Example 1 are secondary processes, and Embodiments 3, 4 and Comparative Example 2 are primary processes. It can be seen from the data in Table 3 that, regardless of the primary process or the secondary process, the torque resistance, fatigue resistance, wear resistance and compression deformation of each embodiment are significantly better than those of the comparative example, and the various data of each embodiment can meet the national standards.
[0170] and, Figure 1 The IP sole finished product of Example 4 of the present invention has high light transmittance.
[0171] The present invention selects low melting polypropylene, that is, homopolymer PP with a melting point between 120-135 degrees Celsius and a specific gravity of 0.9g / cm 3 , using the same processing method (formula see Table 4, process the same as before), an experimental comparison was carried out.
[0172] Table 4 Formula of Comparative Examples 3-6 of the present invention
[0173]
[0174] The performance test results of Comparative Examples 3-6 are shown in Table 5. The light transmittance of the sole samples made of modified homopolymer PP material is shown in Table 5. Figure 2 (Comparative Example 5 IP sole) It can be seen that the samples made in Comparative Examples 3-6 have poor transparency, large shrinkage, and relatively poor other physical properties. In addition, if high melting point homopolymer PP or copolymer PP is used, it is easy to foam at high temperature, but it cannot be dispersed at low temperature.
[0175] Table 5 Sample performance of comparative examples 3-6 of the present invention
[0176]
[0177]
[0178]
[0179] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0180] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A high torque, lightweight and transparent EVA composite foam material for sports shoe soles, characterized in that: The EVA composite material is prepared by foaming, and the EVA composite material includes the following components in parts by weight: 30-50 parts of highly transparent modified copolymer PP; 30-50 parts of ethylene-vinyl acetate copolymer; 15-25 parts of olefin block copolymer; 5-10 parts of anti-wear agent; 0.2-0.5 parts of stearic acid; 0.2-1 parts of stearate; 0.3-1.5 parts of bridging agent; 1.5-6.5 parts of transparent foaming agent; The highly transparent modified copolymer PP is prepared by mixing and granulating highly transparent copolymer PP, isoprene rubber, EPDM rubber and stearic acid; the mass proportion of the highly transparent copolymer PP in the highly transparent modified copolymer PP is not less than 30%; the light transmittance of the highly transparent copolymer PP is not less than 90%, and the melting point is less than 135°C; the specific gravity of the high-torque, lightweight transparent EVA composite foam material for sports shoe soles is less than 0.2g / cm 3 .
2. The high torque, lightweight transparent EVA composite foam material for sports shoe soles according to claim 1, characterized in that: The specific gravity of the ethylene-vinyl acetate copolymer is ≤0.95 g / cm 3 ; The specific gravity of the olefin block copolymer is ≤0.89g / cm 3 .
3. The high torque, light and transparent EVA composite foam material for sports shoe soles according to claim 1, characterized in that: The anti-wear agent is pre-dispersed silicone masterbatch.
4. The high torque, light and transparent EVA composite foam material for sports shoe soles according to claim 1, characterized in that: The bridging agent is 1,4-di-tert-butyl peroxide isopropylbenzene.
5. A method for preparing a high-torque, lightweight, transparent EVA composite foam material for sports shoe soles according to any one of claims 1 to 4, comprising the following steps: Weigh the material components by mass, including 30-50 parts of highly transparent modified copolymer PP, 30-50 parts of ethylene-vinyl acetate copolymer, 15-25 parts of olefin block copolymer, 5-10 parts of anti-wear agent, 0.2-0.5 parts of stearic acid, 0.2-1 parts of stearate, 0.3-1.5 parts of bridging agent and 1.5-6.5 parts of transparent foaming agent; The weighed material components are mixed, granulated, and then foamed to obtain the high-torque, lightweight, transparent EVA composite foam material for the sports shoe sole.
6. The preparation method according to claim 5, characterized in that: The highly transparent modified copolymer PP is prepared in the following manner: Highly transparent copolymer PP, EPDM rubber and stearic acid are mixed at a temperature of 130-135°C, and mixed particles are obtained by granulation; The mixed particles, isoprene rubber and stearic acid are kneaded and granulated again, and the re-granulation temperature is 110-115° C. to obtain highly transparent modified copolymer PP.
7. The preparation method according to claim 5, characterized in that: The foaming is IP injection foaming, and the foaming temperature is 175-180°C.
8. The preparation method according to claim 5, characterized in that: The foaming is MD molding foaming, wherein the small foaming temperature is 165-175°C and the MD molding temperature is 155-165°C.
Citation Information
Patent Citations
Styrene-butadiene copolymer chemical foaming composition containing polystyrene micro-blocks, preparation method and application method thereof
CN101747543A
High-torsion-resistance foaming material and preparation method and application thereof
CN110172202A
